Studi Komparasi Sikap Siswa Sekolah Dasar di Provinsi D.I. Yogyakarta terhadap STEM (Science, Technology, Engineering, and Mathematics) - Muhammad Labib Jalali Khumaidi; Mustamid Mustamid (Journal on Education, 2024)
This research aims to analyze the attitudes of elementary school students in the DIY province towards STEM (Science, Technology, Engineering, and Mathematics) based on gender and student environment. The research design employed is quantitative research using a comparative method. The research sample consists of 187 students from the sixth grade, including 5 elementary schools in the Kulon Progo district and 5 elementary schools in Yogyakarta city. The research findings indicate that (1) the attitudes of male elementary school students in DIY towards STEM are 21.65% in the high category and 78.35% in the moderate category. The attitudes of female elementary school students in DIY towards STEM are 18.89% in the high category and 81.11% in the moderate category. (2) The attitudes of rural elementary school students in DIY towards STEM are 15.48% in the high category and 84.52% in the moderate category. The attitudes of urban elementary school students in DIY towards STEM are 24.27% in the high category and 75.73% in the moderate category. (3) There is no significant difference in the attitudes of elementary school students in DIY towards STEM based on gender differences; the average attitudes of both are in the moderate category. (4) There is no significant difference in the attitudes of rural and urban elementary school students towards STEM; the average attitudes of both towards STEM are categorized as moderate.